MODEL PEMBELAJARAN MATERI SUBYEK UNTUK PENINGKATAN KETRAMPILAN BERFIKIR KONSEPTUAL DALAM PERANCANGAN BANGUNAN - Ahdiat, Dadang (-)
This research is started issues: what forms of subject matter learning model that can be developed to enhance students conceptual thinking skills for prospective professionals of Housing Engineering D3 Program? To be able to develop a teaching model, we need to investigate the characteristics of the subject matter, methods, approaches, evaluation tools, the types of developed conceptual thinking skills, support facilities and problems on the implementation of learning models, as well as the cost and time needed. The developed learning model is expected to increase the students conceptual thinking skills, improve the quality of graduates, and could be used as an example to be developed on similar subjects, and also enhance the professional competence of Housing Engineering D3 program graduates to later compete on the working field. Therefore it is necessary to pay attention on the learning facilities and student learning environment.